2014 International Conference on Electrical Machines (ICEM) 2014
DOI: 10.1109/icelmach.2014.6960172
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of hoisting motors

Abstract: Since 2009 she has been with Konecranes, Finland. Her research interests include electrical machines and drives, energy-efficiency design, and hybridization. Juho Montonen was born in 1988 in Joutseno, Finland. He received the Master of Science (M.Sc.) degree from Lappeenranta University of Technology (LUT), Finland in 2012 and Bachelor of Science (B.Sc.) in 2011. He is currently doctoral student in LUT. He is doing the research concerning about electrical machines and drives. His research work focuses on perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Motor selection is an important consideration and several informative publications discuss the selection and analysis of hoist motors such as for example [25], [26], [27], [28] and [29]. Development of advanced motor designs such as the doubly-fed induction motor [28], which promises enhanced overall efficiency and other advantages in hoist applications, is of special interest.…”
Section: Drive System Backgroundmentioning
confidence: 99%
“…Motor selection is an important consideration and several informative publications discuss the selection and analysis of hoist motors such as for example [25], [26], [27], [28] and [29]. Development of advanced motor designs such as the doubly-fed induction motor [28], which promises enhanced overall efficiency and other advantages in hoist applications, is of special interest.…”
Section: Drive System Backgroundmentioning
confidence: 99%
“…Parallel to the energy saving systems, scientists have investigated other field of energy savings. The article [18] focuses on the energetic efficiency of hoisting mechanisms in industrial applications. A typical duty cycle of the hoist is periodically intermittent.…”
Section: Introductionmentioning
confidence: 99%
“…When a sequential run with constant load takes place, the hoisting mechanism has to be driven by motors designed for S3 duty cycle [12]. Authors of paper [18] investigate the influence of motor's rotor material on the energetic efficiency for a few stack lengths. The conclusion is that because of low operating hours and major share of partial loads, increasing efficiency does not provide notable energy or cost savings.…”
Section: Introductionmentioning
confidence: 99%
“…In mechanical Some teams conducted a research of energetic efficiency of motors which were used in hoisting mechanisms fed by inverters. The research presented in [12] showed, that increasing the energetic effectiveness of motors did not make tangible benefits. It was caused by short times of operation and a large share of partial load of the mechanism.…”
Section: The Hoisting Mechanismmentioning
confidence: 99%